Effect of Literacy in Kenyan Sign Language on Academic Performance of Pupils with Hearing Impairment in Primary Schools in Kenya - M Wawire, Tom; Namunga, Nick (2019)
The purpose of this study was to establish the relationship between li teracy in Kenyan Sign Language (KSL) and academic performance of pupil s with hearing impairment (HI) in public primary schools in western Ke nya. Study objective was to find out the effect of pupils' literacy in Kenya sign language on academic performance. The study employed a mix ed research approach and a descriptive survey design to collect qualit ative and quantitative data. Using purposive sampling technique, 12 he ad teachers, 93 teachers and 108 pupils with HI forming a sample size of 213 respondents. Research instruments used were a Likert scale ques tionnaire and interview schedule. Piloting of the questionnaire was do ne in a public special primary school for the pupils with HI in Birund a School for the Deaf Trans Nzoia. The collected data was analyzed usi ng descriptive statistics of frequencies, percentages, means, standard deviation and Pearson correlation coefficient and inferential statist ics of chi-square using the statistical package for social sciences [S PSS] program of version 23. Qualitative data was analyzed by describin g the emerging themes in relation to the study objectives. The study e stablished that there was significant relationship between pupils' int erpretation of KSL, literacy in KSL and challenges in using KSL and ac ademic performance, all at p<0.05. Therefore, the null hypothesis was rejected and concluded that literacy in KSL significantly influences a cademic performance. The results will help stakeholders in the educati on sector to establish how KSL is used in the teaching of pupils with HI in schools, hence providing valuable data on the current policy and practice in the field of education and training of teachers of the le arners with HI. The following recommendations were made: pupils should be equipped with more literacy skills for the KSL and adequate resour ces and support services be given to the learners.